EKSTRAKURIKULER EMPOWERING DALAM MENINGKATKAN DAYA SAING SEKOLAH (Studi Kasus di SMA Islam Kepanjen Malang): Anharul Ulum - Anharul Ulum (JPPG : Jurnal Pengembangan Profesi Guru, 2022)
Abstract One of the basic problems of society in this modern era is the difficulty of getting a job after graduating from high school (SMA) for students who do not continue their education. SMA Islam Kepanjen has an extracurricular empowering program as a provisioning of skills for preparing the students to enter the world of work. Extracurricular empowering is a product offered by SMA Islam Kepanjen to attract public interest for choosing their education. This research aims to analyze and to describe the concepts of planning, implementation and implication of extracurricular empowering for improving the school competitiveness in SMA Islam Kepanjen Malang. It used a qualitative research with research design of case study. Data was obtained through interview techniques, observation, and documentation. Data analysis used the model of Miles and Huberman, namely data collection, data reduction, data display, and conclusion drawing /verification. Checking the validity of the data used source triangulation. This research shows that (1) the planning of extracurricular empowering activities is by forming a special team, establishing partnerships, conducting coordination meetings for setting goals and objectives, and procuring special facilities and infrastructure to support extracurricular empowering activities. (2) Implementation of extracurricular empowering activities includes the executor of extracurricular empowering activities. They are the head of the empowering section and the instructors from partnership. The implementation of extracurricular empowering activities is scheduled every Saturday without curricular activities for 2 years and the competency test is conducted at the end of the second year. (3) The implication of extracurricular empowering activities is an improving of SMA Islam Kepanjen’s achievements in the non-academic field and an increase in the number of students of SMA Islam Kepanjen around 15-20% each year.